The assessment of autonomic nervous function in patients with gastrointestinal malignancies and its relationship with clinical characteristics - Xiwen, Zhang; Qiyun, Feng; Chuqiao, Li; Anqi, Jiang; Zhenzhen, Wu; Qiong, Deng; Yu, Peng; Chunlin, Wang (Frontiers in Neuroscience, 2025)
IntroductionThe gastrointestinal tract is the organ most extensively distributed by autonomic nerves, and researches have indicated a relationship between automatic nerves and the progression of gastrointestinal cancers. This study aimed to evaluate the autonomic nervous function in patients with gastrointestinal cancer and to explore its relationship with clinical characteristics.MethodsWe employed the Composite Autonomic Symptom Score 31 (COMPASS-31) questionnaire and cardiovascular autonomic reflex tests (CARTs) to evaluate autonomic nervous function, while also conducting a thorough analysis of clinical data.ResultsOur results showed that low white blood cell (WBC) count (OR = 0.461, 95% CI: 0.218–0.976, p = 0.043) and increased maximum tumor diameter (OR = 1.619, 95% CI: 1.025–2.555, p = 0.039) were risk factors for autonomic dysfunction according to the COMPASS-31 assessment. While hypertension (OR = 5.747, 95% CI: 1.186–27.862, p = 0.030) and elevated platelet-to-albumin ratio (PAR) (OR = 1.256, 95% CI: 1.025–1.540, p = 0.028) were identified as independent risk factors for autonomic dysfunction based on the CARTs results. Combining the findings from COMPASS-31 and CARTs revealed that older age (OR = 1.133, 95% CI: 1.015–1.264, p = 0.027) and vascular invasion (OR = 7.706, 95% CI: 1.391–42.684, p = 0.019) were also independent risk factors for autonomic dysfunction.ConclusionOur findings reveal that these specific factors related to gastrointestinal cancers significantly influence autonomic nervous function. It is essential to evaluate autonomic nervous function and its associated risk factors in patients with gastrointestinal malignancies, which provide new insights into the intervention strategies for cancer diseases.